PERMAINAN "WEREWOLF" DALAM BIMBINGAN KELOMPOK: STUDI TINDAKAN UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI INTERPERSONAL REMAJA - Mahadi Sudarsono; Moch. Syihabudin Nuha; Usrotun Diniyah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This study addresses the issue of low interpersonal communication skills among students, specifically nervousness and lack of confidence, through group guidance services using Game-Based Learning (Werewolf game). The study employed Counseling Action Research (PTBK) conducted in two cycles. The subjects were 12 ninth-grade students (Class IX-E) at SMP Negeri 21 Surabaya, selected via purposive sampling based on low initial scores. There was a significant increase in the students' average activity score from 3.5 in Cycle I to 4.16 in Cycle II. Specifically, students in the "High" interpersonal skill category rose drastically from 20% to 53%. The Werewolf game proved effective in improving interpersonal communication skills as it functions as a social interaction simulator that trains persuasion and impression management, particularly when supported by a conducive (informal) environment.